2021
DOI: 10.1002/agj2.20700
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral estimation of soil organic matter and clay content in loess plateau of China

Abstract: Visible and near-infrared reflectance (Vis-NIR) spectroscopy is considered a promising tool for the estimation of soil properties. Soil clay content and soil organic matter (SOM) are main components affecting soil spectra. Accurate assessment of clay content and SOM is essential before achieving accurate prediction for other soil properties. Selecting the proper spectral transformation technique and optimal calibration method are important processes to improve model performance. In this study, a total of 240 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Cao et al [37] proposed a multiple linear regression (MLR)-based hyperspectral estimation model based on the gray correlation for overcoming the interference of abnormal soil samples on the constructing of linear regression models. Wang et al [38] and Sun et al [39] reported that MLR was the best multivariate technique to predict SOM content of soil. However, the above-mentioned research has regarded that there are differences in the optimum hyperspectral estimation models for different soil types and different regions, but the results of PLSR and MLR are preferable and more stable.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [37] proposed a multiple linear regression (MLR)-based hyperspectral estimation model based on the gray correlation for overcoming the interference of abnormal soil samples on the constructing of linear regression models. Wang et al [38] and Sun et al [39] reported that MLR was the best multivariate technique to predict SOM content of soil. However, the above-mentioned research has regarded that there are differences in the optimum hyperspectral estimation models for different soil types and different regions, but the results of PLSR and MLR are preferable and more stable.…”
Section: Discussionmentioning
confidence: 99%